Efficacy and Safety of Wenbu Zhibi Granule in Patients with Ankylosing Spondylitis: A Multicenter, Randomized, Double-blind, Placebo-controlled Trial. (25th November 2021) - Zhang, Helou; Yu, Yang; Du, Weibin; Wu, Fengqing; Zheng, Yang; Ren, Conglin; Zhou, Huateng; Wu, Yijiang; Gao, Yang; Ren, Weifan; Quan, Renfu
Abstract : Background . Ankylosing spondylitis (AS) is a chronic disease in which the column is the main lesion. It is caused by a combination of genetic and environmental factors, mainly involving the axial skeleton, resulting in column rigidity and difficulty in movement, and there may be different degrees of eye, lung, cardiovascular, kidney, and other organ damage. Long-term treatment lacks in ankylosing spondylitis. Wenbu Zhibi granule (WZG) is a prescription handed down from the history of Chinese medicine for thousands of years, which is used to treat the pain of patients with AS and to prevent the further development of the disease. However, there is no scientific evidence based on clinical trials to evaluate the efficacy and safety of WZG for ankylosing spondylitis. Methods/Design . We will conduct a multicenter, randomized, double-blind, placebo-controlled trial to evaluate the efficacy and safety of the WZG in the treatment of AS. We will randomly assign 100 patients with active AS to two groups, treated for 16 weeks. The primary efficacy endpoint is the proportion of subjects who reached 40% improvement criteria proposed by Assessment of SpondyloArthritis International Society (ASAS40) at 16 weeks from baseline, the secondary efficacy endpoint includes ASAS20 response rate, ASAS partial remission response rate, 5/6 improvement criteria proposed by ASAS (ASAS5/6) response rate, and change in the Spondyloarthritis Research Consortium of Canada (SPARCC) MRI spine score, Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI), Ankylosing Spondylitis Disease Activity Score (ASDAS), linear Bath Ankylosing Spondylitis Metrology Index (BASMI), ankylosing spondylitis quality of life (ASQoL). In addition, the time points will be set as baseline, 2 weeks, 4 weeks, 8 weeks, 12 weeks, 16 weeks, 24 weeks, and 48 weeks. Discussion . The results of this study will elucidate the efficacy and safety of WZG and provide an appropriate treatment option for patients with AS. Trial registration: ClinicalTrials.gov ID: https://clinicaltrials.gov/ct2/show/ChiCTR2000041010 . (Chinese Clinical Trail Registry, Registered 16 December 2020, http://www.chictr.org.cn ).